Colitis‐associated colorectal adenocarcinomas frequently express claudin 18 isoform 2: implications for claudin 18.2 monoclonal antibody therapy. Issue 2 (21st April 2021) - Iwaya, Mai; Hayashi, Hiroyuki; Nakajima, Tomoyuki; Matsuda, Kazuyuki; Kinugawa, Yasuhiro; Tobe, Yosuke; Tateishi, Yoko; Iwaya, Yugo; Uehara, Takeshi; Ota, Hiroyoshi
Abstract : Aims: Claudin 18 (CLDN18) is a member of the claudin family of cell surface proteins, which are widely expressed in epithelial cells and play a role in cell–cell adhesion. CLDN18 isoform 2 (CLDN18.2) is specifically expressed in gastric epithelial cells, and is frequently expressed at high levels in gastric adenocarcinoma. On the basis of this, zolbetuximab, a targeted monoclonal antibody, has been developed for patients with CLDN18.2‐positive gastro‐oesophageal adenocarcinoma. Colitis‐associated colorectal adenocarcinomas (CACs) tend to lose intestinal markers and show aberrant gastric mucin expression. Furthermore, clinical trials of human epidermal growth factor receptor 2 (HER2) inhibitor therapy for colorectal carcinoma are ongoing. However, the expression profile of CLDN18.2 and HER2 has not been described in a series of human CACs. Methods and results: We performed immunohistochemistry for CLDN18 and HER2 on 56 consecutive CACs from 55 inflammatory bowel disease patients, and compared the expression profile with that of a control group of 56 sporadic colorectal adenocarcinomas (CRCs). CLDN18.1 expression and CLDN18.2 expression were validated by reverse transcription polymerase chain reaction (PCR) in paraffin‐embedded CRC tissues. CLDN18 was positive in 27% (15/56) of CACs and in 5% (3/56) of sporadic CRCs ( P = 0.004), and CLDN18‐positive CACs were more likely to have lymph node metastasis than CLDN18‐negative CACs (67% versus 36%; P = 0.017). CLDN18 expression was significantly associated with MUC5AC expression ( P < 0.001) and loss of special AT‐rich sequence‐binding protein 2 expression ( P = 0.005) in CACs. CLDN18.2 was expressed in CRCs that were immunoreactive for CLDN18. Only 4% of CACs were immunoreactive for HER2, and no differences were identified in sporadic CRCs. Conclusions: These findings suggest that certain CAC cases may be candidates for targeted zolbetuximab therapy. Abstract :